2023
DOI: 10.1002/ejhf.2794
|View full text |Cite
|
Sign up to set email alerts
|

Bone status in men with heart failure: results from the Studies Investigating Co‐morbidities Aggravating Heart Failure

Abstract: To assess bone status expressed as hip bone mineral density (BMD) in men with heart failure (HF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…The authors disclosed not only worse BMD parameters in every localization in HF patients, but importantly, in these patients, they found significant global and local reductions of BMD as well as worsening of Z-score over time. 11 The current issue of the Journal presents a paper by Loncar et al 12 who reported a retrospective analysis of longitudinal changes of BMD in 141 men with stable chronic HF based on four time-points DEXA scans over the follow-up of 30 months. Patients were also clinically observed for up to 8 years, and bone characteristics were correlated with blood markers and prognosis.…”
Section: Egg or Hen Dilemmamentioning
confidence: 99%
See 1 more Smart Citation
“…The authors disclosed not only worse BMD parameters in every localization in HF patients, but importantly, in these patients, they found significant global and local reductions of BMD as well as worsening of Z-score over time. 11 The current issue of the Journal presents a paper by Loncar et al 12 who reported a retrospective analysis of longitudinal changes of BMD in 141 men with stable chronic HF based on four time-points DEXA scans over the follow-up of 30 months. Patients were also clinically observed for up to 8 years, and bone characteristics were correlated with blood markers and prognosis.…”
Section: Egg or Hen Dilemmamentioning
confidence: 99%
“…The current issue of the Journal presents a paper by Loncar et al 12 . who reported a retrospective analysis of longitudinal changes of BMD in 141 men with stable chronic HF based on four time‐points DEXA scans over the follow‐up of 30 months.…”
Section: Egg or Hen Dilemmamentioning
confidence: 99%
“…Among 47 patients undergoing a re‐evaluation of BMD, a significant reduction in BMD was observed at 30 months. Thus, an assessment of bone status might be of help in the prevention of osteoporosis in HF patients 30 …”
Section: Comorbiditiesmentioning
confidence: 99%
“…Thus, an assessment of bone status might be of help in the prevention of osteoporosis in HF patients. 30…”
mentioning
confidence: 99%